Root Canal Morphology of the Permanent Mandibular Incisors by Cone Beam Computed Tomography: A Systematic Review - Silvia Herrero-Hernández; Nansi López-Valverde; Manuel Bravo; Óliver Valencia de Pablo; Manuel Peix-Sánchez; Javier Flores-Fraile; Juan Manuel Ramírez; Bruno Macedo de Sousa; Antonio López-Valverde (Applied Sciences, 2020)
Knowledge of dental anatomy through the assessment of the anatomic variations of each tooth’s root canal system is essential to undertake endodontic therapy. The aim of this systematic review was to analyze the different studies on the internal morphology of permanent mandibular incisors where Cone-Beam Computed Tomography (CBCT) X-ray imaging is used. Pubmed, CENTRAL, Wiley Library and Web of Science electronic databases were searched for scientific studies included until March 2020. The terms used in the search were: “permanent mandibular incisors”, “root canal morphology” and “cone-beam computed tomography”. The search was limited to studies whose aim was the analysis of the morphology of the root canal system evaluating the parameters of methodology, population, sample, number and configuration. A total of 19 studies met the inclusion criteria. There was a noticeable lack of unanimity in the setting adjustments of each of the CBCT devices used. The presence of two root canals varied from 0.4% to 45%. The most frequent configurations were Vertucci’s Types I, III, II, V, IV, VII and VI. Type VIII configuration was non-existent. CBCT revealed the existence of anatomical symmetry patterns, and there was no unanimity of criteria regarding the presence of a second root canal. Results concerning the presence of a second root canal in the mandibular incisors differ widely, with a possible influence of the geographic area where the study was conducted. The prevalence of a second canal is higher in mandibular lateral incisors than in mandibular central incisors. There was no direct relationship between voxel size (0.125–0.3 mm) and increased prevalence of a second canal.